Cardiovascular compromise in the infection by the human immunodeficiency virus - Valenzuela-Rodríguez, Germán (2023)
Human immunodeficiency virus (HIV) infection was associated with increased morbidity and mortality, predominantly for opportunistic infections, before using antiretroviral therapy. With this, patients have experienced increased survival and cardiovascular compromise too. The etiology of these clinical conditions could be related to the infection itself, adverse events associated with antiretroviral therapy, or adverse events produced by the combination with other drugs. Some of these conditions have an acute onset, and their rapid recognition is vital for a better prognosis.